Adaptasi Pura dalam Menyikapi Modernitas: Refleksi Sosial berdasarkan Teori Emile Durkheim - Tri Suryani; Muhamad Ridwan Effendi (Yayasan Al-Afif, 2025)
Modernity has brought changes to urban social life, including the religious practices of Hindu communities at Pura Aditya Jaya Rawamangun. Technological developments, urban social dynamics, and demands for efficiency have encouraged adjustments in temple management and ritual practices. This study aims to analyze forms of temple adaptation to modernity without losing its sacred function, as well as their impact on social solidarity among Hindus. The study employs a qualitative descriptive approach based on field research through in-depth interviews and direct observation. The findings show that adaptation occurs through adjustments in ritual practices, the use of information technology, more professional facility management, and the provision of worship equipment for devotees from diverse backgrounds. These adaptations do not diminish sacredness but instead strengthen the temple’s social function as a center of integration and moral development. From Emile Durkheim’s perspective, these findings indicate that religion as a social fact is adaptive and continues to play a role in fostering social solidarity and collective consciousness within modern society.